(3YQa GdYHjQ aj YQa GdJYHjQs - (3Ydj Hf GdMSf Hf GdbGSe Hf efUhQ Hf TjN GdYhfjg GdehUdj GdTGaYj, CHh GdMSfs
(3BNQgG (B:s
(3aEf Ydeg , hdYd cKjQ ef GdeWhdGJ de jPcQ ajgG TF eeG JVefg ajg hGddg JYGdi Gdehab ddUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B127 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3JYHjQ GdQDjGs